Re-signifying “Asia” in the Transnational Turn of Asian/American Studies - Lin, Chien-Ting (Review of International American Studies, 2016)
Chien-Ting Lin Re-signifying “Asia” in the Transnational Turn of Asian/American Studies Abstract Bringing inter-Asia cultural studies into conversation with Asian American critique, this paper aims to reframe the critical analysis of the scattered hegemonies of US imperialism in articulating the transpacific historical interconnections. Rather than privileging the US as a primary site of investigation and critique, I draw careful attention to the Cold War conditions of inter-Asia migration as an entry point for discussing how the geopolitics of Taiwanese modernity, from the Cold War up to neoliberal globalization, are inextricably linked to Japanese colonialism, US militarism and modernization, and Chinese globalization. To develop my theoretical and historical (re)conceptualization of “Asia” in Asian/American studies, I look at how the migrant narrative of migrant workers in the nonfiction novel Our Stories speaks to the power dynamics of the US Cold War involvement in Asia, neoliberal globalization, and Taiwan subimperialist relations with its neighboring countries. Whereas Asian American cultural critique offers a new analytics to enable a reconceptualization of Asian America without confining it to an identitarian category, inter-Asia cultural studies redirect critical attention to the historical undercurrents of inter-Asia geopolitics that are largely obscured by the dominant knowledge paradigm of the US Cold War politics in the regions of Asia Pacific.